Dampak Strategi Pemasaran Pariwisata terhadap Peningkatan Kesejahteraan Masyarakat dalam Perspektif Ekonomi Islam (Studi di Pantai Wisata Labuhan Jukung Krui Kabupaten Pesisir Barat) - Is Susanto; Mad Heri; Achmad Fachrudin (FEB Universitas Sultan Ageng Tirtayasa, 2019)
This study aims to analyze the marketing strategy of Labuhan Jukung tourism beach Pesisir Barat Regency and its impact on people's welfare in the perspective of Islamic economics. The results of the study show that the marketing strategy carried out by the manager of Labuhan Jukung Tourism Beach in the Pesisir Barat Regency is by collaborating with parties involved in tourism marketing. The manager implements 4 marketing strategies, that is product strategy, price strategy, promotion strategy and distribution strategy. The impact of this marketing strategy is the increasing public welfare in the Labuhan Jukung Tourism beach. Islamic economics sees that the marketing strategy of Labuhan Jukung Tourism Beach is in accordance with Islamic economic principles. This can be seen from the 4 strategies carried out, that is product strategy, place strategy, price strategy, and promotion strategy, there are no practices that violate Islamic economic principles.